Comparative Evolutionary Genomics of Androgen-Binding Protein Genes - Emes, Richard D.; Riley, Matthew C.; Laukaitis, Christina M.; Goodstadt, Leo; Karn, Robert C.; Ponting, Chris P. (Genome Research, 2004)
Allelic variation within the mouse androgen-binding protein (ABP) α subunit gene (Abpa) has been suggested to promote assortative mating and thus prezygotic isolation. This is consistent with the elevated evolutionary rates observed for the Abpa gene, and the Abpb and Abpg genes whose products (ABPβ and ABPγ) form heterodimers with ABPα. We have investigated the mouse sequence that contains the three Abpa/b/g genes, and orthologous regions in rat, human, and chimpanzee genomes. Our studies reveal extensive “remodeling” of this region: Duplication rates of Abpa-like and Abpbg-like genes in mouse are >2 orders of magnitude higher than the average rate for all mouse genes; synonymous nucleotide substitution rates are twofold higher; and the Abpabg genomic region has expanded nearly threefold since divergence of the rodents. During this time, one in six amino acid sites in ABPβγ-like proteins appear to have been subject to positive selection; these may constitute a site of interaction with receptors or ligands. Greater adaptive variation among Abpbg-like sequences than among Abpa-like sequences suggests that assortative mating preferences are more influenced by variation in Abpbg-like genes. We propose a role for ABPα/β/γ proteins as pheromones, or in modulating odorant detection. This would account for the extraordinary adaptive evolution of these genes, and surrounding genomic regions, in murid rodents.
10.1101/gr.2540304